Honor Thyself - Steel, Danielle (New York : Bantam Dell, 2009)
In the days that follow a tragic accident, a woman who the whole world knows slowly awakens with no memory of who she is. Every detail must be pieced back together--from a childhood in rural Mississippi to the early days of her career, from the unintentional hurt inflicted on her daughter to a fifteen year-old secret love affair that went tragically wrong. But for this woman an extraordinary opportunity has arisen in a life-threatening crisis: a second chance to count her blessings, heal wounded hearts, recapture lost love ... and to live a life that will truly honor others--beginning with herself. --From publisher description.
Keywords: Motion picture actors and actresses -- Fiction; Women novelists -- Fiction; Victims of crimes -- Fiction; Amnesia -- Fiction; Paris (France) -- Fiction; Romance fiction